Effects of microbial-derived long-chain polyunsaturated fatty acids from Aurantiochytrium limacinum BCC52274 and Mortierella sp. on growth and immunity in Litopenaeus vannamei post-larvae - Virak Visudtiphole; Panida Unagul; Sage Chaiyapechara; Waraporn Jangsutthivorawat; Metavee Phromson; Siriporn Tala; Pacharawan Deenarn; Punsa Tobwor; Pisut Yotbuntueng; Surasak Jiemsup; Suganya Yongkiettrakul; Looksorn Koichai; et al. (PLoS ONE, 2025)
The rapid growth of the aquaculture industry has increased the demand for feed ingredients, resulting in a shortage of fishmeal and fish oil, the latter of which serves as a source of essential fatty acids in aquaculture feed. As dietary supplementation of long-chain polyunsaturated fatty acids (LC-PUFA) improved growth and strengthened immunity in marine larvae, alternative sources for LC-PUFA are required to maintain sustainable aquaculture practice. This study explored the use of Aurantiochytrium limacinum BCC52274 (AL) and oil extracted from Mortierella sp. (ARASCO) as the source of LC-PUFA for the Pacific white shrimp Litopenaeus vannamei post-larvae (PLs) by using Artemia as a carrier. The Artemia were first enriched with combinations of AL and ARASCO with varying ratios of DHA:ARA at 100:0, 75:25, 50:50, 25:75, and 0:100, which were designated as Groups A, B, C, D, and E, respectively. The unenriched Artemia in Group R served as a control. The L. vannamei PL1 were fed with these Artemia for 18 days, revealing that the PL18 in Group A contained the highest biomass and average body weight among all feed groups. Meanwhile, other ratios of DHA:ARA supplementation were more beneficial to shrimp immunity, as the PL18 from Group D expressed the highest levels of prophenoloxidase II transcripts among all feed groups. The increasing proportion of ARA in the enriched Artemia also increased the levels of anti-inflammatory eicosanoids, including 15-deoxy-Δ12,14-prostaglandin J2, 11-hydroxyeicosatetraenoic acid (11-HETE), and 12-HETE. When these PLs were infected with white spot syndrome virus (WSSV), the PLs from Groups A, C, D, and E contained lower WSSV copy numbers compared with Group R, suggesting that the supplementation of LC-PUFAs from AL and ARASCO strengthened the immunity of these PLs against viral infection. However, the challenge with Vibrio harveyi resulted in no significant difference in the mean survival rates of PLs in all feed groups. Our results indicate that AL and ARASCO are more sustainable alternative sources of essential fatty acids that can be used strategically to enhance the growth and immunity of L. vannamei PLs.